2023
DOI: 10.3233/jad-221063
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Glutamate Transporter Changes in the Cortical Default Mode Network During the Clinical and Pathological Progression of Alzheimer’s Disease

Abstract: Background: Altered glutamatergic neurotransmission may contribute to impaired default mode network (DMN) function in Alzheimer’s disease (AD). Among the DMN hub regions, frontal cortex (FC) was suggested to undergo a glutamatergic plasticity response in prodromal AD, while the status of glutamatergic synapses in the precuneus (PreC) during clinical-neuropathological AD progression is not known. Objective: To quantify vesicular glutamate transporter VGluT1- and VGluT2-containing synaptic terminals in PreC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…It should be noted that the analyses in Mi et al (2023) used the MMSE as the dependent variable with cyano-PiB and X-34 as independent variables. Here, we used cyano-PiB and X-34 as the dependent variables since their distributions are more like those of other biological variables used in neuroscience studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the analyses in Mi et al (2023) used the MMSE as the dependent variable with cyano-PiB and X-34 as independent variables. Here, we used cyano-PiB and X-34 as the dependent variables since their distributions are more like those of other biological variables used in neuroscience studies.…”
Section: Resultsmentioning
confidence: 99%
“…Using two different independent datasets from published postmortem neurodegenerative disease studies ( Ginsberg et al, 2019 ; Mi et al, 2023 ), we demonstrated how robust regression can be used as an alternative to linear regression when the error distribution of a dependent variable does not meet the assumption of normality. The examples used in the present study show how estimates for regression coefficients, SE, p -values, and R 2 values can be significantly biased using linear regression models when the dependent variable does not meet the assumption of normality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, glutamate also performs neurobiological tasks by regulating motor as well as brain functions [78,79]. However, glutamate overstimulation can also cause neurotoxic processes, which are also observed in some neurodegenerative diseases, including Alzheimer's and Parkinson's disease [80][81][82][83].…”
Section: Excitotoxicitymentioning
confidence: 99%